Potassium-competitive Acid Blockers: A New Therapeutic Strategy for Helicobacter pylori Eradication - Byeong Yun Ahn; Soo-Jeong Cho (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
The escalating prevalence of clarithromycin resistance in cases of Helicobacter pylori, insufficient acid suppression, and pharmacodynamic variations secondary to inter-individual differences in CYP2C19 polymorphism collectively contribute to suboptimal eradication rates observed with proton pump inhibitor (PPI)-based therapy. Compared with PPIs, potassium-competitive acid blockers (PCABs) produce rapid, potent, and long-lasting suppression of gastric acid through reversible inhibition of gastric H+, K+-ATPase. PCAB-based therapy results in significant inhibition of acid secretion and has therefore emerged as a novel and effective approach for H. pylori eradication. In this study, we review the efficacy and safety profile of PCAB-based eradication regimens comprising vonoprazan, tegoprazan, and fexuprazan.